Development of Learning Media Based on Animal Classification Interactive Animal Park at Kademangan 01 State Elementary School - Akmal, Muhammad Fauzi; Gunadi, Andi Ahmad (LPPM UIKA Bogor, 2024)
The purpose of this research is to develop interactive learning media based on animal parks to classify animals based on their food types. The research method used is Research and Development using the Borg and Gall model. The data collection technique used is to provide assessment instruments to media experts, material expert, and questionnaires to fourth grade student. The results obtained through the media expert research instrument obtained a score of 78% which included decent criteria, while the material expert obtained a score of 82% with very feasible criteria, and the student assessment in the small group obtained a score 86% which included very feasible criteria and the large group obtained a score of 83% which included very feasible criteria.